Benefits of BIM in construction projects - Vimonsatit, Vanissorn; Chai Mui Foo, A. (ISEC Press, 2015)
This paper presents findings of an investigation into benefits of using Building Information Modelling (BIM) in construction projects. The research methodology includes a review of BIM development and achievement in construction industry, questionnaire survey, interview, and content analysis of secondary data. Data was collected and analyzed to identify the various benefits reflected from BIM implementation in addressing common problems experienced by the construction industry. The review and survey results indicate that a high frequency of occurrence of time and cost overruns occur in construction projects. Contributing factors were mainly rework, poor planning, documents delivery and approval, constructability issues, resources and weather condition. While some of the factors were unpreventable, BIM could be used as a tool to eliminate problems causing time and cost overruns. Various project benefits have been reflected through the content analysis of project case studies. It was found that time was the most positively influenced by the use of BIM followed by coordination, procurement, communication, cost and change of scope of the project, and lastly, risk.